2008
DOI: 10.1007/s11368-008-0004-6
|View full text |Cite
|
Sign up to set email alerts
|

Speciation of Zn, Cu, and Pb in the soil depending on soil texture and fertilization with sewage sludge compost

Abstract: Background, aim, and scope Heavy metal (HM) mobility in soil depends on the HM species in it. Therefore, knowledge of the HM speciation in soil allows the prediction of HM impact on the environment. HM speciation in soil depends on the metal chemical origin, soil texture, and other factors such as the origin and level of soil contamination. Recently, the problem of organic waste utilization is of great importance as the amount of this recyclable material is continually increasing. One of the possible ways of r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(22 citation statements)
references
References 37 publications
0
22
0
Order By: Relevance
“…For instance, relatively high sludge amendment rates on sandy soils may pose risks to water quality because the amounts of Cd, Ni, Pb and Zn leached from the soil to the groundwater may increase. Significant negative effects on the mobilities and potential availabilities of heavy metals have been found only for sandy soils and high sludge amendment rates (Brazauskiene et al, 2008). Jalali and Arfania (2011) thought that amendment of sludge to sandy soil may pose little risk of groundwater becoming contaminated with Cd, Ni and Pb.…”
Section: Influence Of Sludge Amendment On Heavy Metal Risk In Groundwmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, relatively high sludge amendment rates on sandy soils may pose risks to water quality because the amounts of Cd, Ni, Pb and Zn leached from the soil to the groundwater may increase. Significant negative effects on the mobilities and potential availabilities of heavy metals have been found only for sandy soils and high sludge amendment rates (Brazauskiene et al, 2008). Jalali and Arfania (2011) thought that amendment of sludge to sandy soil may pose little risk of groundwater becoming contaminated with Cd, Ni and Pb.…”
Section: Influence Of Sludge Amendment On Heavy Metal Risk In Groundwmentioning
confidence: 99%
“…In addition, some soil properties, such as high cation exchange capacity (CEC) also had a relatively sufficient retention capacity to heavy metals (Antoniadis et al, 2010). The uptaken amount of heavy metals in soil and edible plant tissue exhibited higher level in sandy loam soil than clayey loam soil, implying that soil type plays important role in mobility, potential availability even uptaken ability to heavy metal by plant grown in amended soil (Bai et al, 2010;Brazauskiene et al, 2008;Singh and Agrawal, 2007). Results obtained by Li et al (2012) showed that level in the grain were found to be in the order of Zn > Cu > Cd, but for the straw the order was Cd > Cu > Zn, indicating different organs or tissues exhibited difference in bioconcentration factor for heavy metal.…”
Section: Organic Matter Plays Crucial Role In Availability Of Heavy Mmentioning
confidence: 99%
“…From 2007 to 2014, many studies have reported the heavy metals risk associated with the amendment of sludge to soil (Alcantara et al, 2009;Antoniadis et al, 2007;Brazauskiene et al, 2008;Carbonell et al, 2009;Lag-Brotons et al, 2014;Oladeji et al, 2012;Yeganeh et al, 2010). However, there is certain boundedness on the conclusions obtained by these researchers mentioned above.…”
Section: Introductionmentioning
confidence: 99%
“…Soil pH has a direct impact on the mobility of metals as it affects their solubility and their capacity to form chelates in soil [14]. It has been reported that more than 50 % of the Pb fraction was residual fraction by the MSWC amendments, but the amount of exchangeable Pb increased over the course of the experiment [15]. Present study showed that the bioavailability of metals in MSWC treatments increased over the incubation.…”
Section: Soil Metal Characteristicsmentioning
confidence: 46%